Application of Islamic Economic Concepts as a Role Model in Increasing the Wooden Furniture Business in Bengkalis - Saputra, Andrian; Alma’arif (El-Qish: Journal of Islamic Economics, 2024)
This article discusses the role of fiqh knowledge in managing the muamalah process, including in the context of buying and selling. The business in the field of wooden furniture is really hot because this business is very promising and produces large profits. Especially in Bengkalis Regency, an area that is an island in Riau Province. Even though this area is small, it has a lot of natural wealth. For example, mining for oil, palm oil, and furniture materials, namely quality trees and wood to be used in making houses and other furniture materials. The method used in this research is descriptive qualitative using library research. In practice, not many furniture business processes apply Islamic principles in running the business. For example, illegal logging of forests is carried out, the impact of which is detrimental to residents. In fact, in Islam itself, all businesses carried out are prohibited from destroying the environment and harming other people for the sake of personal interests and some groups. For this reason, this research was carried out to analyze and review the extent of the wooden furniture business practices in Bengkalis based on Islamic fiqh, both the implementation and transactions of the furniture business carried out.